2016
DOI: 10.9734/ajee/2016/30830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste Engine Oil on the Microflora and Physico-chemical Quality of Soils from two West African Countries

Abstract: A study of the bioremediation of diverse levels of simulated contamination of waste engine oil (WEO) in soil using natural attenuation, bioaugmentation, mycoremediation and phytoremediation was carried out. This required a preliminary study of the microbiological and physico-chemical quality of waste engine oil contaminated soils from as it were, a "naturally" contaminated site, as a check that the characteristics of the "natural" and simulated samples match. Thus, WEO contaminated soil samples were randomly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The degree of acidity and alkalinity of soil is a very important property affecting many other physicochemical and biological properties and can as well be used as index to assess soil quality and severe hydrocarbon contamination results to high soil acidity (low pH) and high moisture content, low total organic carbon and total organic matter all implying low soil fertility which in turn implies low agricultural productivity and reduced source of livelihood in the affected area (Ikuesan et al, 2019). The hydrocarbon in the contaminated samples resulted to an increase in the total organic carbon contents of the contaminated samples which could be as a result of increase in bulk of carbon and organic matter in them (Chijioke and chinenye, 2016). Muhammad et al, 2016 showed that motor oil treatment had no significant effect on the soil texture.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of acidity and alkalinity of soil is a very important property affecting many other physicochemical and biological properties and can as well be used as index to assess soil quality and severe hydrocarbon contamination results to high soil acidity (low pH) and high moisture content, low total organic carbon and total organic matter all implying low soil fertility which in turn implies low agricultural productivity and reduced source of livelihood in the affected area (Ikuesan et al, 2019). The hydrocarbon in the contaminated samples resulted to an increase in the total organic carbon contents of the contaminated samples which could be as a result of increase in bulk of carbon and organic matter in them (Chijioke and chinenye, 2016). Muhammad et al, 2016 showed that motor oil treatment had no significant effect on the soil texture.…”
Section: Introductionmentioning
confidence: 99%